Establishment of a hemiparasite Rhinanthus alectorolophus and its density‐dependent suppressing effect on a grass: A case study from golf roughs - Hejduk, Stanislav; Bitomský, Martin; Pornaro, Cristina; Macolino, Stefano (Agronomy journal, 2020)
Suppression effect of hemiparasites on grasses is a phenomenon, that can be utilized to increase biodiversity of various grassland systems. Host suitability, environmental effects, and hemiparasite abundance most likely influence the impact of parasitism on host height and biomass. However, the role of these factors is unclear in field conditions. We studied host suitability, establishment rates, and effects of a hemiparasitic plant Greater yellow rattle [ Rhinanthus alectorolophus (Scop.)] (RA) on canopy height and biomass of a grass tall fescue (Festuca arundinacea Schreb.) in five trials with manipulated fertilization conducted in golf roughs. Particularly, we examined how grass height and biomass changed with increasing hemiparasite abundance. On average, grasses (nine in total) were better hosts than legumes (four in total). Tall fescue belonged to the group of better hosts. The average establishment rate of Rhinanthus plants ranged from 4.4 to 24.8% regardless of fertilization treatments. In fertilization trials, Rhinanthus did not affect grass height but weakly suppressed grass biomass in non‐fertilized plots. The relationship between grass height/biomass and Rhinanthus abundance was best described by a logarithmic decay model. The suppressive effect tended to saturate (negative density dependence) in plots where the Rhinanthus abundance was very high. However, such high densities were quite rare and low Rhinanthus abundances were usually insufficient to substantially suppress grass growth. Our results indicate that we should aim for at least 50 Rhinanthus plants per 1 m2 to achieve desirable effects on biodiversity and that Rhinanthus performance will be better when nutrients are rather limiting.